Pelaksanaan Program Pusaka Sakinah dalam Pandangan Hukum Islam (Studi Kasus di KUA Kecamatan Palang Kabupaten Tuban) - Karmuji, Karmuji; Muhyidin, Muhyidin (Universitas Sunan Drajat Lamongan, Indonesia, 2022)
Implementation of the Sakinah Heritage Program in the View of Islamic Law (Case Study at KUA Palang District, Tuban Regency)” This is the result of field research that aims to answer questions about how to implement the Sakinah heritage program in KUA Palang District and how to analyze Islamic law on the implementation the sakinah heritage program at the KUA in Palang District.This research is a qualitative field research. The data in this study were obtained through observation, interviews, and documentation, and then processed and analyzed using descriptive analysis techniques and deductive thinking patterns.From the results of the study it can be concluded that the guidance of Pusaka Sakinah at the Office of Religious Affairs (KUA) of Palang District is carried out after the marriage, which is carried out for two days using the